“The ban is there, but it is not there”: perceptions of cigarette users and tobacco vendors regarding ban on the sale of loose cigarettes in India - Sakhuja, Mayank; Macauda, Mark M.; Thrasher, James F.; Hebert, James R.; Pednekar, Mangesh S.; Gupta, Prakash C.; Friedman, Daniela B. (Frontiers in Public Health, 2024)
Introduction Banning the sales of loose cigarettes is recommended by Article 16 of the World Health Organization – Framework Convention on Tobacco Control. This study aims to understand the perceptions of cigarette users and tobacco vendors regarding such a ban. Methods Using a systematic recruitment and interview protocol, we interviewed cigarette users (n = 28) and tobacco vendors (n = 28) from two Indian cities where sales of loose cigarettes were banned (Mumbai) or not banned (Delhi). Separate semi-structured interview guides were used for users and vendors. Interview questions focused on reasons for purchasing loose cigarettes, preference for buying and selling loose vs. packs, thoughts on the necessity of banning loose cigarettes, and the perceived impact of the policy ban for vendors and cigarette users. We performed thematic analysis and used NVivo for organizing transcript coding. Results The main reasons users cited for purchasing loose cigarettes were financial constraints, social restrictions (fear of getting caught), and limiting cigarette consumption. In Mumbai, awareness of the existing ban was poor among both users and vendors. Those who were aware did not think the policy had been implemented. Users thought that loose cigarettes promoted smoking initiation and prevented them from quitting. Both users and vendors reported that a ban on loose cigarettes would reduce cigarette consumption and promote quit attempts as it would not be possible for everyone to purchase packs because of financial and social reasons. Conclusion Users in both cities reported easy access to and widespread availability of loose cigarettes. Low awareness of the ban in Mumbai suggested inadequate enforcement. A country-wide ban on the sale of loose cigarettes could be highly effective in preventing smoking initiation and promoting quitting.